Polydatin Reduces Cardiotoxicity and Enhances the Anticancer Effects of Sunitinib by Decreasing Pro-Oxidative Stress, Pro-Inflammatory Cytokines, and NLRP3 Inflammasome Expression - Quagliariello, Vincenzo; Berretta, Massimiliano; Buccolo, Simona; Iovine, Martina; Paccone, Andrea; Cavalcanti, Ernesta; Taibi, Rosaria; Montopoli, Monica; Botti, Gerardo; Maurea, Nicola (Frontiers in Oncology, 2021)
Renal cell carcinoma (RCC) represents the main renal tumors and are highly metastatic. Sunitinib, a recently-approved, multi-targeted Tyrosine Kinases Inhibitor (TKi), prolongs survival in patients with metastatic renal cell carcinoma and gastrointestinal stromal tumors, however a dose related cardiotoxicity was well described. Polydatin (3,4',5-trihydroxystilbene-3-β-d-glucoside) is a monocrystalline compound isolated from Polygonum cuspidatum with consolidated anti-oxidant and anti-inflammatory properties, however no studies investigated on its putative cardioprotective and chemosensitizing properties during incubation with sunitinib. We investigated on the effects of polydatin on the oxidative stress, NLRP3 inflammasome and Myd88 expression, highlighting on the production of cytokines and chemokines (IL-1β, IL-6, IL-8, CXCL-12 and TGF-β) during treatment with sunitinib. Exposure of cardiomyocytes and cardiomyoblasts (AC-16 and H9C2 cell lines) and human renal adenocarcinoma cells (769‐P and A498) to polydatin combined to plasma-relevant concentrations of sunitinib reduces significantly iROS, MDA and LTB4 compared to only sunitinib-treated cells (P<0.001). In renal cancer cells and cardiomyocytes polydatin reduces expression of pro-inflammatory cytokines and chemokines involved in myocardial damages and chemoresistance and down-regulates the signaling pathway of NLRP3 inflammasome, MyD88 and NF-κB. Data of the present study, although in vitro, indicate that polydatin, besides reducing oxidative stress, reduces key chemokines involved in cancer cell survival, chemoresistance and cardiac damages of sunitinib through downregulation of NLRP3-MyD88 pathway, applying as a potential nutraceutical agent in preclinical studies of preventive cardio-oncology.